In Operando GIXRD and XRR on Polycrystalline In52Pd481. Issue 15 (8th July 2014) - Ivarsson, Dennis C. A.; Neumann, Matthias; Levin, Alexander A.; Keilhauer, Toni; Wochner, Peter; Armbrüster, Marc
Abstract A combined approach of grazing incidence X‐ray diffraction (GIXRD) and X‐ray reflectivity (XRR) under in operando conditions on polycrystalline materials is presented. This approach allows tracking of material changes of amorphous or crystalline nature in the near‐surface region. Crystalline phases formed in operando can be identified by X‐ray diffraction, while by XRR measurements information about the thickness and the density of overlayers is obtained. The setup also allows collection of data generated with higher incident angles which permit a direct comparison of the changes close to the surface and in the bulk of the materials. Results for the composition In52Pd48 – a mixture of the intermetallic compounds InPd and In3Pd2 catalyzing the steam reforming of methanol – in reducing atmosphere and under methanol steam reforming (MSR) conditions are presented. InPd exhibits a dynamic behavior, reacting to changes in atmosphere and temperature. The combination of GIXRD and XRR proves to be a powerful tool to examine model catalysts under catalytically relevant conditions providing complementary information to other methods.